2016
DOI: 10.1103/physrevb.94.144423
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous and planar Righi-Leduc effects in Ni80Fe20 ferromagnets

Abstract: In this paper, we report experimental evidence of anomalous and planar Righi-Leduc effects on NiFe. The Righi-Leduc effect is the thermal analog of the Hall effect, in which the electric current is replaced by the heat current and the electric field by the temperature gradient. When the material is ferromagnetic, it is well known that there are two other contributions to the Hall voltage which depend on the orientation of the magnetization. These two extra contributions are called the anomalous Hall effect whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…A voltage drop will be developed at the ends of the electrode (C and D point) due to the spin current injection into the electrode and the corresponding ISHE in it with large spin orbit coupling (such as Pt, Bi). However, it seems that no signal of the 2π periodicity of ISHE was observed in the experiment 23 . Therefore, we directly use Eq.…”
Section: Fitting and Analysismentioning
confidence: 74%
See 3 more Smart Citations
“…A voltage drop will be developed at the ends of the electrode (C and D point) due to the spin current injection into the electrode and the corresponding ISHE in it with large spin orbit coupling (such as Pt, Bi). However, it seems that no signal of the 2π periodicity of ISHE was observed in the experiment 23 . Therefore, we directly use Eq.…”
Section: Fitting and Analysismentioning
confidence: 74%
“…Then, in order to fit the experimental data in Ref. 23 , we used thermocouple effect to transform the temperature gradient at both ends of the electrode into the electric potential. Finally, we use the formula of total voltage to fit with the experimental data and found that it fits well.…”
Section: Identification Of Spin Effects In the Anomalous Righi-leduc mentioning
confidence: 99%
See 2 more Smart Citations
“…This is the so-called longitudinal spin-Seebeck effect (LSSE) 3,4 . Although the validity of the SSE has been challenged by the parasitic thermal electric effect and thermal Hall effect, such as the anomalous Nernst effect (ANE) [4][5][6] , magnon Hall effect (MHE) 7,8 and anomalous Righi-Leduc effect (ARLE) 9,10 , it has been verified in many YIG-based heterostructures that LSSE remains a reliable methodology to investigate pure spin current phenomena in the framework of spin caloritronics 5,11 .…”
Section: Introductionmentioning
confidence: 99%